Um modelo multifatorial para medir a satisfação dos consumidores de supermercados - Santos, José Wendel (2016)
The objective of this study was to propose a multifactorial model for measuring consumer satisfaction supermarket. The development of the proposed model was systematized in five stages: literature review; in-depth research with key informants; preliminary structure of the model; operationalization of the model; and statistical analysis of data from your application. The results of this study demonstrated that the model has a structure composed of 31 attributes grouped in five factors: store atmosphere; product; attendance; convenience and facilities; and security. These factors together explained 89.07% (expectation) and 91.29% (perception) the variability in the original data, besides presenting significant internal consistency, because all the Cronbach’s alpha coefficients encountered exceeded the minimum limit of satisfactoriness. Operationally, the model proposed in this study proved effective because the information acquired from your application in a supermarket enabled the formulation of management strategies to improve service quality and consequently customer satisfaction.